Evaluating the effectiveness of coastal protection structures in flood mitigation using hydrodynamic modeling: A case study in a tropical environment - Samera, Samsuddin Sah; Khairul Nizam, Abdul Maulud; Zulkarnain, Hassan; Nurul Nadrah Aqilah, Tukimat; Yaseen, Zaher Mundher (Elsevier Ltd, 2025)
The coastal zone is complex and vulnerable to flooding, especially in low-lying areas. This research aimed to assess the effectiveness of coastal protection structures as mitigating factors through the application of the hydrodynamic model, MIKE 21. The model utilizes numerical methods to analyze scenarios involving bathymetry, tidal effects, river discharge, digital elevation model (DEM), and sea level rise (SLR). Three scenarios were outlined: the first, K1, represents a simulation without a coastal protection structure; the second, K2, includes the existing coastal protection structure; and the third, K3, presents a modified coastal protection structure designed for the study location. The K3 scenario was segmented into two regions: the northern region (NA) and the southern region (SA), both of which utilize hard and soft engineering coastal protection approaches, respectively. The results demonstrated that K2 and K3 significantly reduced flood areas, decreasing the potential inundation zones in the NA from 228 ha to 304 ha and in the SA from 31 ha to 10 ha, respectively, compared to K1. Statistical analysis (Friedman Test) showed a significant difference between K1 and K2 (chi-square = 4.0, p < 0.05), which validated the models' inclusion of coastal structures for flood risk assessment. In brief, hydrodynamic modeling that incorporates coastal structures can effectively evaluate the risk of coastal flooding in impacted areas while also enhancing the accuracy and reliability of the output.